Development and validation of the SDLD score: a simplified tool to predict successful endoscopic papillectomy in ampullary lesions :focused communication - Vu Trung, Kien; Abou-Ali, Einas; Gulla, Aiste; Soares, Kevin; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Halimi, Asif; Masaryk, Viliam; Bruno, Marco J.; Pérez-Cuadrado-Robles, Enrique; Bolm, Louisa; et al. (Gastrointestinal endoscopy, 2025)
Background and Aims - Endoscopic papillectomy (EP) is the standard treatment for noninvasive ampullary lesions (ALs), whereas advanced cases require surgery. Managing ALs is challenging and may lead to over- or undertreatment. We developed a score to identify the best candidates for endoscopic or surgical treatment. - Methods - We analyzed 447 patients who underwent EP. The cohort was randomly split into a training set (n = 325) and validation set (n = 122). Logistic regression identified predictors for incomplete resection (R1), which were incorporated into a 4-item score. Performance was assessed using the area under the receiver-operating characteristic curve (AUROC). - Results - Independent predictors for R1 included size ≥30 mm (S), high-grade dysplasia and/or invasive cancer (D), laterally spreading-lesion (L), and bile or pancreatic duct dilation (D), which we named the SDLD score. ALs with 0 to 1 points had the highest complete resection rates (training, 86.0%; validation, 88.5%), whereas ≥2 points significantly increased R1 rates (training, 52.0%; validation, 57.7%; P < .001). The AUROC was 0.792 (training) and 0.708 (validation). - Conclusions - The SDLD score predicts R1 in EP and aids in treatment decisions.